MANAGEMENT OF PRODUCTION AND ECONOMIC ACTIVITIES OF AN ENTERPRISE: FROM THEORY TO PRACTICE - Гарват, Ольга; Коваль, Анатолій (SWorldJournal, 2025)
The article is devoted to substantiating the feasibility of introducing management of production and economic activities of enterprises. Today, the activities of industrial enterprises of Ukraine take place in conditions of war, characterized by a high l